4566 Group Ghazal - Lishan, Stuart (Cornfield Review, 2014)
Collaborators: Samantha Lynch [or Stover, her name pre marriage], Whitney Taylor, Stevie Evans, Brittany Long, Brian Wild, Janay Dyer, Ruth albright, Melanie Waits, Andrew Pinkerton, and Ashley Irvin